Effect of paricalcitol and calcitriol on aortic wall remodeling in uninephrectomized ApoE knockout mice - Becker, Luis Eduardo; Koleganova, Nadezda; Piecha, Grzegorz; Noronha, Irene L.; Zeier, Martin; Geldyyev, Aman; Kökeny, Gabor; Ritz, Eberhard; Groß-Weissmann, Marie-Luise (American journal of physiology. Renal physiology, 2011)
Despite an only minor reduction in the glomerular filtration rate, uninephrectomy (UNX) markedly accelerates the rate of growth of atherosclerotic plaques in ApoE−/− mice. It has been suggested that vitamin D receptor (VDR) activation exerts an antiproliferative effect on vascular smooth muscle cells, but the side effects may limit its use. To assess a potentially different spectrum of actions, we compared the effects of paricalcitol and calcitriol on remodeling and calcification of the aortic wall in sham-operated and UNX ApoE−/− mice on a diet with normal cholesterol content. Sham-operated and UNX mice were randomly allotted to treatment with solvent, calcitriol (0.03 μg/kg) or paricalcitol (0.1 μg/kg) 5 times/wk intraperitoneally for 10 wk. Semithin (0.6 μm) sections of the aorta were analyzed by 1) morphometry, 2) immunohistochemistry, and 3) Western blotting of key proteins involved in vascular calcification and growth. Compared with sham-operated animals (5.6 ± 0.24), the wall-to-lumen ratio (x100) of the aorta was significantly higher in solvent- and calcitriol-treated UNX animals (6.64 ± 0.27 and 7.17 ± 0.81, respectively, P < 0.05), but not in paricalcitol-treated UNX (6.1 5 ± 0.32). Similar differences were seen with respect to maximal plaque height. Expression of transforming growth factor (TGF)-β1 in aortic intima/plaque was also significantly higher in UNX solvent and UNX calcitriol compared with sham-operated and UNX paricalcitol animals. Treatment with both paricalcitol and calcitriol caused significant elevation of VDR expression in the aorta. While at the dose employed paricalcitol significantly reduced TGF-β expression in plaques, calcitriol in contrast caused significant vascular calcification and elevated expression of related proteins (BMP2, RANKL, and Runx2).
Gesehen am 10.03.2022